Penerapan Undang-Undang Informasi Dan Transaksi Elektronik (ITE) Terhadap Korban Sekstorsi Di Dunia Maya - Ade Irwina Safitri; Kuswanto; Muhammad Chalil (Jurnal Kajian Hukum Dan Kebijakan Publik | E-ISSN : 3031-8882, 2023)
Sextortion comes from two words sex (sex) and extortion (blackmail) which means sexual blackmail. Sextortion is blackmail carried out with the aim of obtaining sexual content (photos/videos), obtaining money from the victim, and/or engaging in sex with the victim, by threatening to distribute photos or videos of the victim containing pornographic content that were previously owned by the perpetrator. Sextortion is a new crime that has entered cyberspace or cyberspace (cybercrime). This research was conducted to find out how legal regulations and protection are carried out by the state for victims of sextortion crimes in cyberspace using normative legal research using secondary data with library study techniques, namely in the form of collecting secondary data that is related to the problem being researched and classified according to cataloguing. From this research, it can be seen that there is no clarity regarding the regulation of the crime of sextortion, the weakness of the legal umbrella and legal certainty regarding sextortion cases makes it difficult to obtain justice for victims of sextortion. Therefore, it is necessary to perfect the law regarding clear jurisdiction regarding the special law or lex sepcialis for the crime of sextortion, so that it can minimize and criminalize law enforcement in future sextortion cases with various new and different modes.